The effect of electronic body protector and gamification on the performance of taekwondo athletes - Sevinç, D.; Çolak, M. (International Journal of Performance Analysis in Sport, 2019)
The aim of the study is to analyze changes in the performance of taekwondo athletes after training with an electronic body protector and the effects of gamification on this change. The study included 15 licensed taekwondo athletes between the ages of 10 and 13 training in a private taekwondo hall. The three techniques most frequently used in matches were selected according to the level of difficulty, and the athletes followed a three-month training program. In addition, five athletes were interviewed to determine the effects of using the electronic body protector system and the gamification components on their performance. The results showed significant difference between the mean scores of all three taekwondo techniques over time. The data obtained through interviews indicated that training with an electronic body protector improved the participants` condition and technical skills, and also helped them learn the correct use of the techniques. The electronic body protector was observed to indirectly affect performance. The participants emphasized fair scoring for everyone as the electronic body protector was perceived as an objective system. Announcement of the scores of each measurement on the scoreboard was reported to increase competition, improvement and motivation.